2004
DOI: 10.1007/s00429-004-0423-0
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative analysis of granule cell axons and climbing fiber afferents in the turtle cerebellar cortex

Abstract: The turtle cerebellar cortex is a single flat sheet of gray matter that greatly facilitates quantitative analysis of biotylinated dextran amine labeled granule cell and olivocerebellar axons and Nissl-stained granule and Purkinje neurons. On average, ascending granule cell axons are relatively thicker than their parallel fiber branches (mean +/- SD: 0.84 +/- 0.17 vs 0.64 +/- 0.12 microm, respectively). Numerous en passant swellings, the site of presynaptic contact, were present on both ascending and parallel f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 36 publications
(42 reference statements)
2
21
0
Order By: Relevance
“…Conduction velocities of mammalian parallel fibers are 0.18 -0.27 m/s, although their lengths are not proportional to brain size. In turtles, parallel fibers have a mean diameter of 0.64 Ϯ 0.12 m and have been observed to transverse nearly the entire Cb (Tolbert et al 2004), forming roughly 100 synapses every millimeter. The optical responses following ML stimulation are consistent with continuous activation of the Cb along a narrow transverse beam from lateral edge to lateral edge.…”
Section: Responses To Io Stimulation Are Oriented Sagittally In Thementioning
confidence: 99%
See 2 more Smart Citations
“…Conduction velocities of mammalian parallel fibers are 0.18 -0.27 m/s, although their lengths are not proportional to brain size. In turtles, parallel fibers have a mean diameter of 0.64 Ϯ 0.12 m and have been observed to transverse nearly the entire Cb (Tolbert et al 2004), forming roughly 100 synapses every millimeter. The optical responses following ML stimulation are consistent with continuous activation of the Cb along a narrow transverse beam from lateral edge to lateral edge.…”
Section: Responses To Io Stimulation Are Oriented Sagittally In Thementioning
confidence: 99%
“…The repeating modules of Cb each receive excitatory input from mossy fibers, which in turn stimulate granule cells (Walsh et al 1972). Axons from granule cells ascend to the ML synapse with PCs during the ascent and bifurcate to form parallel fibers (Huang et al 2006;Tolbert et al 2004). Stimulating mossy fibers activates a local patch of PCs via ascending axons of granule cells (Bower and Devor 2003;Cohen and Yarom 1998;Rokni et al 2007), as shown by correlated activity of granule cells and their overlying PCs (Lu et al 2005).…”
Section: Responses To Granule Cell Layer Microstimulation Maymentioning
confidence: 99%
See 1 more Smart Citation
“…However, unlike in most other species, the turtle cerebellar cortex is relatively small and unfoliated, a morphological feature that permits physiological [6][7][8][9] and anatomical studies [5,21,29,30] to answer fundamental questions of cortical structure and function. Here, the total Purkinje cell number in the cerebellum counts were not estimated, but rather were counted from the entire cerebellum from serial reconstructions using calbindin immunohistochemistry.…”
Section: Discussionmentioning
confidence: 96%
“…Its cerebellum (Cb) is uniquely suited for a topographic analysis because it is an unfoliated sheet of cortex covering the fourth ventricle, unlike most vertebrates whose cerebella is highly foliated. In spite of this simplification, the turtle Cb retains the same cellular organization of cerebella of higher vertebrates [5], consisting of a molecular layer, a Purkinje cell (PC) layer, and an internal granule cell layer. It is connected to each side of the brainstem by a broad attachment to the optic tectum and the dorsolateral part of the rostral medulla.…”
Section: Introductionmentioning
confidence: 98%